Communication Experiences of DATA-Waivered Physicians with Community Pharmacists: A Qualitative Study. (3rd February 2020) - Ventricelli, Daniel J.; Mathis, Stephanie M.; Foster, Kelly N.; Pack, Robert P.; Tudiver, Fred; Hagemeier, Nicholas E.
Abstract: Background: Patients engaged in evidence-based opioid use disorder (OUD) treatment can obtain prescriptions for buprenorphine containing products from specially trained physicians that are subsequently dispensed by community pharmacists. Despite the involvement of physicians and community pharmacists in buprenorphine prescribing and dispensing, respectively, our understanding of their interactions in this context is limited. Objective: To qualitatively describe the communication and collaborative experiences between Drug Addiction Treatment Act 2000 (DATA)-waivered physicians and community pharmacists from the perspective of the physician. Methods: Ten key informant interviews were conducted with DATA-waivered physicians practicing in Northeast Tennessee. A semi-structured interview guide was used to explore communication and collaborative experiences between the physicians and community pharmacists. Interviews were audio recorded and transcribed verbatim. A coding frame was developed using concepts from the scientific literature and emerging codes from physician interviews. Interviews were coded using NVivo 11, with the data subsequently organized and evaluated for themes. Results: Four themes were identified: (1) mechanics of communication; (2) role specification and expectations; (3) education and understanding; and (4) climate of clinical practice. Physician-pharmacist communication primarily occurred indirectly through patients or staff and perceived challenges to collaboration included; lack of trust, stigma, and fear of regulatory oversight. Physicians also indicated the two professionals may lack clear roles and responsibilities as well as common expectations for treatment plans. Conclusions: Communication between DATA-waivered physicians and community pharmacists is influenced by multiple factors. Further research is warranted to improve physician-community pharmacist collaboration (PCPC) in the context of OUD pharmacotherapy and addiction treatment.